THE EFFECT OF CONCENTRATED OWNERSHIP ON BANK PROFITABILITY IN INDONESIA - Amanda, Michelle Priscilla; Lam, Serafina; ., Rinaningsih; Adelina, Yang Elvi (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
This paper examines the association between concentrated ownership and the profitability of banks in Indonesia during the period from 2012 to 2018 with a total sample of 93 banks or 651 observations. This study applies the Random Effect regression method, and reveals a non-significant association between concentrated ownership and bank profitability as measured by ROA and ROE. It indicates that a majority of shareholders tend to use their power to exploit minority shareholders, which can also strengthen the monitoring effect. However, the regression also indicates that there is a significant non-linear relationship between concentrated ownership and profitability when measured by ROE. There is a mixed-effect between concentrated ownership and profitability in the case of Indonesian banks. Moreover, a regression is also utilized with dummy variables of concentrated ownership (FIN and IND) to assess the difference between non-financial institution ownership and financial institution ownership. The results show no significant difference in cases. This can be caused by institutional ownership (financial institutions), which only acts as a short-term trader that emphasizes short-term profits. Therefore, its existence as a shareholder is not any different to the presence of non-financial institution ownership. The findings of this study show that the application of POJK No. 56/POJK.03/2016 regarding Share Ownership of Commercial Banks which regulates the maximum limit of concentrated ownership in banks may not work effectively in strengthening bank performance.